UPAYA PENCEGAHAN DAN PENANGGULANGAN DAMPAK PEMANASAN GLOBAL - Nawa Suwedi (Jurnal Teknologi Lingkungan, 2005)
Global warming can be influented by natural and human activities. Effect andimpact of it should be consider for all countries of the world . To reduce the global warming effects some activities will be shown in this paper. They will be divided into prevention and tackling activities.